1997
DOI: 10.1021/ma9618944
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Radical Cyclopolymerization of N-Allyl-N-phenylmethacrylamide in the Presence of SnCl4 and l-Menthol

Abstract: Asymmetric induction was examined in the cyclopolymerization and cyclocopolymerization of N-allyl-N-phenylmethacrylamide (PAMA) with dimethyl 2,2′-azobis(isobutyrate) in benzene in the presence of L-menthol and SnCl4. Optical activity ([R]D ) -0.3 to -5.6) was observed for poly(PAMA)s formed in the radical polymerization of the PAMA/SnCl4/L-menthol system. The PAMA monomer unit was incorporated exclusively as a five-membered ring into the highly cyclized poly(PAMA)s (degree of cyclization (DC) ) 95-98%) obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Recently, ring construction in vinyl polymers has been proven to be particularly useful for stereochemical control in free‐radical polymerization 1–4. In an earlier article,5 we found that asymmetric induction is caused in the polymer main chain by radical cyclopolymerization of N ‐allyl‐ N ‐phenylmethacrylamide (APMA) in the presence of SnCl 4 and L ‐menthol as the chiral compound.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, ring construction in vinyl polymers has been proven to be particularly useful for stereochemical control in free‐radical polymerization 1–4. In an earlier article,5 we found that asymmetric induction is caused in the polymer main chain by radical cyclopolymerization of N ‐allyl‐ N ‐phenylmethacrylamide (APMA) in the presence of SnCl 4 and L ‐menthol as the chiral compound.…”
Section: Introductionmentioning
confidence: 98%
“…A catalytic amount of chiral cobalt complex was shown to induce configurational chirality in a radical polymerization for the first time. The induction of configurational chirality to the polymer chain by radical polymerization using a chiral radical species is unprecedented though there are examples based on chiral monomer structure, chiral additives that presumably work as Lewis acids, , and a chiral inclusion complex . Further work is in progress in order to clarify the mechanism, to enhance the induction efficiency, and to find a way to control tacticity in the polymerization of more versatile monomers using a radical species.…”
mentioning
confidence: 99%
“…The optical activity and the content of trans -structure in the main chain of the polymers were comparable to those of the polymers synthesized by using 1 . N -Phenyl -N -allylmethacrylamide ( 22 ) was shown to be a remarkable diene monomer for radical cyclopolymerization to give a polymer having fi ve -membered ring structures in the main chain with high cyclization selectivity of 95 -98% [66] . The enantioselective polymerization in the presence of SnCl 4 /( − ) -menthol gave optically active polymers with an optical rotation of [ α ] D − 5.6 ° .…”
Section: Methacrylatesmentioning
confidence: 99%